Evaluasi Kualitas Layanan Website Airyrooms.com dengan Menggunakan Metode Webqual 4.0 dan Importance And Performance Analysis (IPA) - Andry Lesmana Japrianta; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of E-commerce was rapid, especially in Indonesia. Airyrooms.com was one of the e-commerce engaged in transportation and hospitality that provides online sales services. The analysis was conducted by using several variables in webqual, namely usability, information quality, and service interaction quality with the aim of knowing the value of service quality at Airyrooms.com site from the user's perception by doing a descriptive analysis. Meanwhile, IPA was used as an analysis of conformity analysis, gap analysis, and IPA quadrant. The data were obtained by distributing questionnaires and getting the samples of 100 respondents. Descriptive statistical results showed that the variables of usability, information quality, and service interaction quality were among in the categories of high enough to high. The results of IPA quadrant analysis show that the indicators of errors, efficiency, accuracy, and responsiveness were in â€œKeep up the Good Workâ€ quadrant, the indicators of learnability and trusted were in the "Possible Overkill" quadrant, the indicators of the imaged conveyed to the user, appearance, accessibility, relevance, empathy were in the "Lowest Priority" quadrant, the indicators of the ease of use and navigation, satisfaction, and representational were in the "Priorities for Improvements" quadrant. From these results, recommendations for improvements to the indicators in "Lowest Priority" and "Priorities for Improvements" quadrants, so that the indicator was in the â€œKeep up The Good Workâ€ quadrant